Addressing the dichotomy of brand love. (November 2019) - Junaid, Muhammad; Hussain, Khalid; Hou, Fujun
Is love experienced for a brand an emotion (casually labeled as brand love)? Yes, /may be! Is "brand love" an emotion? No.